The determinants of the integrated reporting as a tool for high quality of financial reporting (Revista Galega de Economía)
This study tries to offer a critical evaluation of the advances in the context of integrated reporting as a new element of accounting and social information on the social sustainability of companies. Based on a dataset of 380 observations from 95 companies listed on the Johannesburg Stock Exchange (JSE), covering the 4-year period 2017-2020, this study evaluates antecedents related to corporate governance: board of directors, the duplication of functions of chairman and CEO, the proportion of women on the board of directors, the committee for appointing members of the board of directors, the remuneration committee, the number of bank meetings. The results of our research show that companies with a high level of board independence, a separation of the roles of chairman and CEO, a high number of board meetings, a CSR index and a very high ESG performance high are more likely to have high-quality integrated reports.